Assessment of cancer related fatigue in children and adolescents - Perdikaris, Pantelis; Papadatou, Danai; Patiraki, Elisabeth; Merkouris, Anastasios; Kosmidis-Vasilatou, E.; Matziou, Vasiliki N. (My University, 2008)
Cancer related fatigue has received limited clinical attention, although it is described as one of the most distressing symptoms children and adolescents are suffering during their treatment. AIM The aim of this study was (a) to assess the change in fatigue scores during cancer treatment according to children's and adolescents' perspectives, (b) to describe the possible causes of fatigue from children's and adolescents' view. MATERIAL-METHOD The present study was an ongoing prospective study. The research group consisted of 40 children aged 7-12 years and 29 adolescents with cancer who are followed up in an oncology clinic of a Greek children's hospital. After parental consent was obtained, data were collected using the Children's Fatigue Scale (CFS), Adolescents' Fatigue Scale (AFS) and a sociodemographic data form. RESULTS The children with cancer reported a statistically significant increase in fatigue scores during their treatment (z=-3.38, P=0.001). Similarly, adolescents' fatigue levels increased significantly during their treatment (z=-2.22, P=0.026). No other demographic factor, except gender in the children group (z=-2.04, P=0.042 for the beginning of treatment and t=2.43, P=0.02 for the end of treatment) found to increase significant the fatigue scores. CONCLUSIONS Cancer treatment was found to increase significant children's and adolescents' fatigue levels. Medical procedures and hospital environment seemed to be major causative factors for experiencing fatigue by the children and adolescents with cancer during their treatment.
Εκτίμηση της κόπωσης παιδιών και εφήβων με καρκίνο
Keywords: Cancer